2018
DOI: 10.1071/wr18032
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors affecting adult female white-tailed deer survival in the Northern Great Plains

Abstract: Context Documenting cause-specific mortality and deriving survival estimates for a population are both vital to understanding potential restrictions to population growth. Survival varies among populations of the same species and depends on several factors, including climatic events, density-dependent and density-independent factors, observed predator composition and whether recreational hunting occurs. Therefore, understanding factors affecting adult survival and estimating survival rates at biologically impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Although there are several predators of white-tailed deer, coyotes are the main predator of adult white-tailed deer in the Northern Great Plains (Moratz et al 2018) and are also an important predator of white-tailed deer neonates in the Northern Great Plains (Brinkman et al 2004;Grovenburg et al 2011) and throughout their range (Gingery et al 2018;Kautz et al 2019;Warbington et al 2017). Furthermore, coyotes are reported to have substantial impacts on white-tailed deer neonate populations at local scales (Chitwood et al 2015;Kilgo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several predators of white-tailed deer, coyotes are the main predator of adult white-tailed deer in the Northern Great Plains (Moratz et al 2018) and are also an important predator of white-tailed deer neonates in the Northern Great Plains (Brinkman et al 2004;Grovenburg et al 2011) and throughout their range (Gingery et al 2018;Kautz et al 2019;Warbington et al 2017). Furthermore, coyotes are reported to have substantial impacts on white-tailed deer neonate populations at local scales (Chitwood et al 2015;Kilgo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The low mortality rate and absence of observed hunter harvest as a mortality source in 2016 was unexpected and difficult to account for. We are not aware of any study documenting a greater rate of annual survival for adult females than we observed in 2016 (0.96), but rates ≥0.88 have been reported in New Brunswick, Canada (0.92 and 0.89; Whitlaw et al 1998), West Virginia (0.88; Campbell et al 2005), South Dakota (0.88; Moratz et al 2018), and Kentucky, USA (0.91; Haymes et al 2018). Following the hemorrhagic disease outbreak in summer 2012, annual harvest of adult females in Sussex County declined by approximately 30% in 2012 and 2013, began to increase in 2014–2016, and appeared to stabilize in 2017 and 2018 at a level slightly above pre‐2012 annual harvest (E. W. Ness, Delaware Division of Fish and Wildlife, unpublished data).…”
Section: Discussionmentioning
confidence: 54%
“…Hunter harvest accounted for 86% of mortality in exurban Illinois, USA (Storm et al 2007), 46% of mortality in an agricultural region in Minnesota, USA (Brinkman et al 2004), and 70% of mortalities in agricultural regions of South Dakota, USA, and Minnesota (Grovenburg et al 2011). In contrast, separate research in South Dakota reported natural causes (i.e., disease, starvation, predation) were a more prominent source of mortality than hunter harvest in adult females (DePerno et al 2000, Moratz et al 2018).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…could provide a reprieve from nutritional bottlenecks during winter related to snow depth. Few studies explicitly examine effects of winter variables on deer survival in agricultural areas, although Moratz et al (2019) did report elevated mortality during March-April of years with relatively harsher winters in the Northern Great Plains.…”
Section: Modelmentioning
confidence: 99%